Specific and general transfer of perceptual-motor skills and learning between sports: A systematic review. (March 2022) - Oppici, Luca; Panchuk, Derek
Abstract: Objectives: Sport developmental models contend that participating in different sports promotes expertise development, implying positive skill transfer between sports. This study conceptualizes and examines how specific and general transfer occur and interact between sports in the short- (skill transfer) and long-term (learning transfer). Specific transfer is predicated on the perception and utilisation of specifying information in a transfer task, while general transfer relies on non-specifying, "general" information. Furthermore, the study examined how certain conditions (affordance similarity, perceptual-motor exploration and expertise) promote the transfer process. Design: Systematic literature review. Methods: An electronic search was performed on SPORTDiscuss, Pubmed/MEDLINE, and Scopus. Studies were included if participants performed a transfer task in a sport different to the sport they learned a skill in. Results: A total of 17 studies of low-to-moderate quality were included. Most studies showed specificity of transfer between sports with overlapping affordances and generality of transfer between sports with no overlapping affordances (for a given skill). Only 2 studies examined how perceptual-motor exploration supported specific transfer, and 2 examined transfer for (subsequent) learning with contrasting results. Six studies indicated an expertise effect, showing higher transfer in skilled vs less-skilled athletes. Conclusions: This review provides a conceptualization of specificity and generality of transfer, and initial evidence on how transfer emerges between sports in the short-term. It provides little information on the general-specific interaction in the short-term, and does not provide any insights on how transfer emerges in mid- and long-term. As such, no inference regarding sport developmental models can be made. The low-to-moderate quality of the studies requires caution in interpreting these findings. We encourage future research to investigate general and specific transfer longitudinally, recruiting populations with different expertise levels to further advance our current understanding. Highlights: Short-term transfer between sports is towards specificity when affordances overlap and generality when do not overlap. A limited number of studies examined specificity-generality interaction showing that general can support specific transfer. A limited number of studies examined how practicing a sport influences skill learning in a new sport with contrasting results. Current literature on perceptual-motor transfer between sports does not provide insights regarding sport developmental models. Current literature is limited to short-term transfer and future research should expand to longer time scales.